2007
DOI: 10.1007/s11249-007-9233-x
|View full text |Cite
|
Sign up to set email alerts
|

A Refined Friction Modeling for Lubricated Metal Forming Process

Abstract: In spite of the existence of a well-developed realistic friction model, it has only been applied to the simple geometric problems, such as the axisymmetric and plane strain conditions, where the formulations of lubricant transport can be decomposed into two characteristic equations. Accordingly, a unified procedure of combining the current lubrication/friction model and finite element code of metal forming has been developed in this article for either steady or unsteady three-dimensional process including both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…The quality of the products and the efficiency of the drawing process depend on several parameters. Friction regimes encountered during deep drawing in particular are known to be extremely complex [1] and [2]. This is as a result of the inherent factors, such as the contact pressure, sliding velocity, surface roughness at sheet metal and tool interface, material properties of the tool and the blank, and the properties of the lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the products and the efficiency of the drawing process depend on several parameters. Friction regimes encountered during deep drawing in particular are known to be extremely complex [1] and [2]. This is as a result of the inherent factors, such as the contact pressure, sliding velocity, surface roughness at sheet metal and tool interface, material properties of the tool and the blank, and the properties of the lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…The values of H t , A and p n in the work zone can be determined from the above lubrication/friction analysis, regardless of whether the tooling/workpiece surfaces are in contact. Yang [16] further described the procedure of lubrication/ friction analysis during the stretch forming process. The surface roughness in the free deformation region of the workpiece (R qf ) is given by Eq.…”
Section: Solution Proceduresmentioning
confidence: 99%
“…Numerical results showed that the inclusion of microwedge in the analysis provides a good agreement with the experimental measurements. Yang [16] and Yang [17] developed a unified procedure of combining a new tribological model and finite element code of metal forming for either steady or unsteady process. The availability of the new friction model was proved by an axisymmetric stretch forming process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations